Brecciated lineaments in Washington Land, North Greenland, and their relation to Nares Strait - Hurst, John M. (Meddelelser om Grønland. Geoscience, 1982)
Linear crush zones at Kap Jefferson suggest strike-slip movement transverse to Nares Strait. Other parallel lineaments, fjords and valleys occur in North Greenland and may have similar structures in them. These may have been areas of incipient strike-slip movement related to an early compressional phase in the formation of the Nares submarine rift valley. These lineaments are approximately perpendicular to Palaeozoic folds and inferred gneissic trends. They may be incipient transform faults, controlled by the interplay between regional plate tectonic stresses at the time, and the influence of pre-existing structures. Island and across North Greenland. The mid- to late Palaeozoic Ellesmerian